The Development of a Selalu Hemat Energi E-Learning-based Instructional Material for Enhancement Learning Result of Students with Hearing Impairment - Eko Julianto Wibowo (Jurnal Penelitian dan Pengembangan Pendidikan Luar Biasa, 2017)
This research was aimed at developing a e-learning-based instructional material of junior high school in the grade VII of students with hearing impairment. Some problems of this study were: 1) the students do not understand how to identify some energy sources (heat, electricity, light and earth) existing in the environment, as result learning outcomes cannot be achieved optimally. 2) the learning media needs increasing quantity and quality. The objectives were to describe: 1) the design process of teaching materials based on integrated e-learning with a theme of Selalu Hemat Energi (Always Saving Energy). 2) the feedback of the material expert, the practitioner of special education of hearing impairment students and the instructional media expert, 3) the test response for small groups and field tests, and 4) analyze the effectiveness of the products developed. The data was collected through questionnaires, evaluation of students, pretest and posttest. The data were analyzed with descriptive qualitative, descriptive statistical analysis t-test. From the material expert, the product was very good. From the practitioner expert, it was very good. From learning media expert’s feedback, it was good. Test results of small group was very good. The assessment results of field test were very good. The test results with SPSS 17 card was at the significance level of 5%. Wide scale test results using t-test showed pretest and posttes 41.66 and 85.09, so that, Ho rejected. In other words, there were significant differences between student learning outcomes before and after being used the teaching materials.Penelitian ini bertujuan untuk mengembangkan materi pembelajaran berbasis pembelajaran e-learning di kelas VII siswa tuna rungu. Beberapa masalah dalam penelitian ini adalah: 1) siswa tidak mengerti bagaimana mengidentifikasi beberapa sumber energi (panas, listrik, cahaya dan bumi) yang ada di lingkungan, akibatnya hasil pembelajaran tidak dapat dicapai secara optimal. 2) media pembelajaran membutuhkan peningkatan kuantitas dan kualitas. Tujuannya adalah untuk mendeskripsikan: 1) proses perancangan bahan ajar berbasis e-learning terpadu dengan tema Selalu Hemat Energi. 2) umpan balik ahli materi, praktisi pendidikan khusus tuna rungu dan ahli media pembelajaran. 3) try out untuk kelompok kecil dan uji lapangan, dan 4) menganalisis keefektifan produk yang dikembangkan. Data dikumpulkan melalui kuesioner, evaluasi siswa, pretest dan posttest. Data dianalisis dengan deskriptif kualitatif, uji statistik deskriptif t-test. Menurut pakar materi dan pakar praktisi produk sangat bagus. Dari umpan balik pakar media pembelajaran, produk dikategorikan sangat bagus. Hasil uji kelompok kecil itu sangat bagus. Hasil penilaian uji lapangan sangat bagus. Hasil tes dengan SPSS versi 17 berada pada tingkat signifikansi 5%. Hasil pengujian skala luas menggunakan uji t menunjukkan pretest dan posttes 41,66 dan 85,09, sehingga Ho ditolak. Dengan kata lain, ada perbedaan yang signifikan antara hasil belajar siswa sebelum dan sesudah digunakan bahan ajar.